The Innovation of Arabic Debate Learning Using TalkPal AI - Naseha, Siti Durotun; Ghofur, Abdul; Mu'at, Mu'at; Rizal, Muhammad Fatkhur; Prismana, IGL Putra Eka (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2024)
The rapid and innovative development of technology presents its own challenges, especially when applied in the field of education, specifically the use of TalkPal AI in Arabic debate learning. TalkPal AI offers an innovative approach that can help students develop debating skills and Arabic fluency through real-time feedback. The purpose of this research is to describe the use of TalkPal AI in learning Arabic debate to enhance students' Arabic debating skills. The approach used is descriptive qualitative, with data collected through observation, interviews, documentation, and questionnaires. The research population consists of 28 third-semester students from the Arabic Language Education (PBA) program, with a sample of 12 students from class B. The results of the study show that 83% of respondents felt aided by the use of TalkPal AI, significantly improving their debating skills and language proficiency. Despite some technical challenges related to internet connectivity, TalkPal AI provides a more flexible, effective, and interactive learning experience. This research concludes that TalkPal AI is an effective innovation in supporting Arabic debate learning among students.